Isolation and Expression Analysis of CYP9A11 and Cytochrome P450 Reductase Gene in the Beet Armyworm (Lepidoptera: Noctuidae). Issue 1 (28th August 2015) - Zhao, Chunqing; Feng, Xiaoyun; Tang, Tao; Qiu, Lihong
Abstract : Cytochrome P450 monooxygenases (CYPs ), as an enzyme superfamily, is widely distributed in organisms and plays a vital function in the metabolism of exogenous and endogenous compounds by interacting with its obligatory redox partner, CYP reductase (CPR). A novel CYP gene ( CYP9A11 ) and CPR gene from the agricultural pest insect Spodoptera exigua were cloned and characterized. The complete cDNA sequences of SeCYP9A11 and SeCPR are 1, 931 and 3, 919 bp in length, respectively, and contain open reading frames of 1, 593 and 2, 070 nucleotides, respectively. Analysis of the putative protein sequences indicated that Se CYP9A11 contains a heme-binding domain and the unique characteristic sequence (SRFALCE) of the CYP9 family, in addition to a signal peptide and transmembrane segment at the N -terminal. Alignment analysis revealed that Se CYP9A11 shares the highest sequence similarity with CYP9A13 from Mamestra brassicae, which is 66.54%. The putative protein sequence of Se CPR has all of the classical CPR features, such as an N -terminal membrane anchor; three conserved domain flavin adenine dinucleotide (FAD), flavin mononucleotide (FMN), and nicotinamide adenine dinucleotide phosphate (NADPH) domain; and characteristic binding motifs. Phylogenetic analysis revealed that Se CPR shares the highest identity with Ha CPR, which is 95.21%. The SeCYP9A11 and SeCPR genes were detected in the midgut, fat body, and cuticle tissues, and throughout all of the developmental stages of S. exigua . The mRNA levels of SeCYP9A11 and SeCPR decreased remarkably after exposure to plant secondary metabolites quercetin and tannin. The results regarding SeCYP9A11 and SeCPR genes in the current study provide foundation for the further study of S. exigua P450 system.